Minimally Invasive, Isolated Tricuspid Valve Redo Surgery: A Safety and Outcome Analysis - Färber, Gloria; Tkebuchava, Sophie; Dawson, Rodolfo Siordia; Kirov, Hristo; Diab, Mahmoud; Schlattmann, Peter; Doenst, Torsten (The Thoracic and Cardiovascular Surgeon, 2018)
Background Isolated tricuspid valve (TV) surgery is considered a high risk-procedure. The optimal surgical approach is controversial. We analyzed our experience with isolated TV redo surgery performed either minimally invasively (redo-MITS) or through sternotomy.Methods We retrospectively analyzed all patients with previous cardiac surgery who underwent redo-MITS (n = 26) and compared them to redo-Sternotomy (n = 17). A group of primary-MITS (n = 61) served as control.Results The redo-MITS approach consisted of a right anterolateral mini-thoracotomy, transpericardial right atrial access, and beating heart TV surgery without caval occlusion. Redo-MITS patients were oldest and had the most comorbidities (EuroScore II: 9.83 ± 6.05% versus redo-Sternotomy: 8.42 ± 7.33% versus primary-MITS: 4.15 ± 4.84%). There were no intraoperative complications or conversions to sternotomy in both MITS groups. Redo-Sternotomy had the highest 30-day mortality (24%), the poorest long-term survival, and the highest perioperative complication rate. Redo-MITS did not differ in perioperative outcome from primary-MITS. Multivariable logistic regression analysis identified redo-Sternotomy (odds ratio [OR] = 9.76; 95% confidence interval [CI] 1.88–63.26), liver cirrhosis (OR = 9.88; 95% CI 2.20–54.20), and body mass index (BMI) (OR = 1.16; 95% CI 1.02–1.35) as independent predictors of 30-day mortality. The Cox model revealed redo-Sternotomy (hazard ratio [HR] = 2.67; 95% CI 1.18–6.03), liver cirrhosis (HR = 3.31; 95% CI 1.45–7.58), and pulmonary hypertension (HR = 2.26; 95% CI 1.04–4.92) as risk factors for poor long-term survival. TV surgery significantly reduces NYHA class.Conclusion Minimally invasive, isolated TV surgery as reoperation without caval occlusion and on the beating heart can be safe and may improve clinical outcome.
Keywords: valve surgery; reoperation; cardiopulmonary bypass